EFEKTIVITAS SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SAKIP) DI SEKRETARIAT DAERAH KABUPATEN WAJO - Monalisa Br, Andi Mitha; Madani, Muhlis; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThis study purposed to find out and analyze the Effectiveness of the Performance Accountability System of Government Agencies in increasing Local Government Accountability in Wajo Regency. The type of research used descriptive qualitative with data collection techniques through interviews and observations. The results of this study showed that the implementation of the Performance Accountability System for Government Agencies (SAKIP) at the Regional Secretariat of Wajo Regency had not effectively. As shown in the following three dimensions: 1) The overall goal achievement had been carried out in stages related to the implementation of SAKIP but was not optimal because it was still focused on improving the Planning and Measurement stage related to the implementation of SAKIP. 2) The integration of processes and procedures related to socialization were not according to expectations, and one of the obstacles was the response from the leadership of the Regional Apparatus to attend activities related to the implementation of SAKIP and only sent to be represented so that communication was not optimal. 3) The adaptation carried out in the implementation of SAKIP had not run effectively. This was because the availability of facilities and infrastructure based on IT connections was not adequate even though office equipment and supplies were adequate and there was still a lack of guidance on human resources. Keywords: Effectiveness, Performance Accountability System for Government Agencies